2014
DOI: 10.1136/bjophthalmol-2014-305718
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of retinal oxygen saturation in normal and treated glaucomatous eyes

Abstract: Retinal oximetry measurements using SRO are highly reproducible in both treated glaucomatous and normal eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The analysis of oxygenation by quadrant was very important on the research of various ocular diseases. Our study suggested that the repeatability and reproducibility of oxygen saturation retinal oximetry measurements for retinal arterioles and venules in normal monkeys were high, which was similar to reports on human eyes [ 17 20 ]. Yip et al [ 14 ] assess the determinants of retinal vessel oximetry measurements and their reliability with an Oxymap T1 Retinal Oximeter in 188 eyes of normal Asian subjects and found that the ICC values ranged from 0.89 to 0.99 for intragrader reliability and 0.85 to 0.96 for intravisit repeatability.…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of oxygenation by quadrant was very important on the research of various ocular diseases. Our study suggested that the repeatability and reproducibility of oxygen saturation retinal oximetry measurements for retinal arterioles and venules in normal monkeys were high, which was similar to reports on human eyes [ 17 20 ]. Yip et al [ 14 ] assess the determinants of retinal vessel oximetry measurements and their reliability with an Oxymap T1 Retinal Oximeter in 188 eyes of normal Asian subjects and found that the ICC values ranged from 0.89 to 0.99 for intragrader reliability and 0.85 to 0.96 for intravisit repeatability.…”
Section: Discussionsupporting
confidence: 89%
“…The newest studies showed better results on the reproducibility than older studies (Goharian et al. ; Turksever et al. ).…”
Section: Discussionmentioning
confidence: 90%
“…; Goharian et al. ), although the reliability may be affected by factors such as the angle of gaze. Palsson et al.…”
Section: Discussionmentioning
confidence: 99%